Diffusion-weighted MR imaging findings of kidneys in patients with early phase of obstruction - Bozgeyik, Zulkif; Kocakoc, Ercan; Sonmezgoz, Fitnet (Elsevier Ireland Ltd, 2009)
Background: Diffusion-weighted (DW) magnetic resonance (MR) imaging is an MR technique used to show molecular diffusion. The apparent diffusion coefficient (ADC), as a quantitative parameter calculated from the DW MR images. The purpose of this study is to evaluate the ability of DW MR imaging in early phase of obstruction due to urolithiasis. Materials and methods: Twenty-six patients with acute dilatation of the pelvicalyceal system detected by intravenous urography were included in this study. MR imaging was performed using a 1.5 T whole-body superconducting MR scanner. DW imaging can be performed using single-shot spin-echo, echo-planar imaging (EPI) sequences with the following diffusion gradient b values: 100, 600, 1000 s/mm(2). Circular region of interest (ROI) was placed in the renal parenchyma for the measurement of ADC values in the normal and obstructed kidney. For statistical analyses, Paired t test were used. Results: In spite of obstructed kidneys had the lower ADC values compared to normal kidneys, these alterations were statistically insignificant. Conclusion: We did not observe significantly different ADC values of early phase of obstructed kidneys compared to normal kidneys. (C) 2008 Published by Elsevier Ireland Ltd.
Keywords: Diffusion-weighted MRI; Kidney; Urolithiasis; Obstruction